RNA interference of NADPHsingle bondcytochrome P450 increased deltamethrin susceptibility in a resistant strain of the Chagas disease vector Triatoma infestans - Varela, Gonzalo M. (2024)
Fil: Varela, Gonzalo Matías. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Cátedra de Bioquímica y Biología Molecular; Argentina.